PENGARUH METODE BERCERITA TERHADAP PERILAKU ANAK KELOMPOK B DI TK WIDYA SHANTI KUMARA - Luh Ika Windayani (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The development of children's behavior is influenced by intellectual development and reasoning. Children have not been able to optimally apply abstract principles concerning right and wrong, as well as other moral and social orders. Therefore, training is needed for them on how to behave morally in certain contexts. Cultivation of morals in childhood with a variety of moral behavior is accepted and supported. Such planting is precisely done through stories. Stories are very effective in influencing the way children think and behave because they enjoy listening to stories even though they are read repeatedly. Repetition, children's imagination, and the value of the closeness of the teacher or parent make stories effective in influencing their thinking. This study aims to determine the effect of the storytelling method on the behavior of group B children in Kindergarten Widya Shanti Kumara. The data collection methods used in this research were observation, interview and documentary. The method of observation that is carried out directly makes observations which include all activities of focusing attention on an object by using all the senses or by using other aids. Interview method, which is to get information by asking the respondent directly. The documentary method is a method used to find data on matters in the form of notes, magazines, newspapers, and other books. The results of data analysis resulted in the effect of the storytelling method on the behavior of group B children in Kindergarten Widya Shanti Kumara. Keywords: Storytelling Method, Child Behavior